The Semantics of Social Media Reactions among Baby Boomers, Gen X, Millennials, and Gen Z: An Exploratory Sequential Mixed-Methods Study - Obenza, Brandon N; Carpizo, Ivy Joy; Ivy Rose Galleros; Elaiza, Monica Mascariñas; Princess Fuertes Terando (Canadian Journal of Language and Literature Studies, 2025)
In the fast-changing world of social media, reactions, including "like," "love," "haha," "wow," "care," "sad," and "angry," are not only icons but also a modern vocabulary of emotions. To what degree do different age demographics comprehend and utilize these phrases within the linguistic framework? This research reveals a significant gap in understanding how emojis are interpreted across different age cohorts, including Baby Boomers, Generation X, Millennials, and Generation Z. To bridge this gap, a sequential exploratory mixed-methods approach was utilized, beginning with qualitative theme analysis from interviews, followed by a quantitative survey with 660 respondent across four age demographics. The findings indicate notable generational differences: Millennials and Gen Z interpret reactions with greater flexibility, irony, humor, or intense emotion, while Baby Boomers and Gen X regard them literally as direct emotional support. Moreover, they use these emojis to downplay the most severe judgments and bring in social bonding. These findings have implications for the growth of intergenerational communication, providing platform providers, marketers, and educators with essential knowledge to overcome generational differences in online contexts.